Free vibration analysis of laminated stiffened cylindrical panels using finite element method - Tuan, Trinh Anh; Quoc, Tran Huu; Tu, Tran Minh (Vietnam Journal of Science and Technology, 2016)
A study on the free vibration analysis of stiffened laminated composite cylindrical shell is described in this paper. The eight-noded isoparametric degenerated shell element is developed to model both shell panel and stiffeners by using the degenerated solid concept based on Reissner-Mindlin assumptions which taking to account the shear deformation and rotatory effect. Numerical results are presented and comparison is made with the published results from the literature and the good agreement is found. Parametric studies considering different geometrical variables of shell and stiffeners have also been carried out.